Oxygen‐Evolving Mesoporous Organosilica Coated Prussian Blue Nanoplatform for Highly Efficient Photodynamic Therapy of Tumors. Issue 5 (22nd February 2018) - Yang, Zhen Lu; Tian, Wei; Wang, Qing; Zhao, Ying; Zhang, Yun Lei; Tian, Ying; Tang, Yu Xia; Wang, Shou Ju; Liu, Ying; Ni, Qian Qian; Lu, Guang Ming; Teng, Zhao Gang; et al.
Abstract: Oxygen (O2 ) plays a critical role during photodynamic therapy (PDT), however, hypoxia is quite common in most solid tumors, which limits the PDT efficacy and promotes the tumor aggression. Here, a safe and multifunctional oxygen‐evolving nanoplatform is costructured to overcome this problem. It is composed of a prussian blue (PB) core and chlorin e6 (Ce6) anchored periodic mesoporous organosilica (PMO) shell (denoted as PB@PMO‐Ce6). In the highly integrated nanoplatform, the PB with catalase‐like activity can catalyze hydrogen peroxide to generate O2, and the Ce6 transform the O2 to generate more reactive oxygen species (ROS) upon laser irradiation for PDT. This PB@PMO‐Ce6 nanoplatform presents well‐defined core–shell structure, uniform diameter (105 ± 12 nm), and high biocompatibility. This study confirms that the PB@PMO‐Ce6 nanoplatform can generate more ROS to enhance PDT than free Ce6 in cellular level ( p < 0.001). In vivo, the singlet oxygen sensor green staining, tumor volume of tumor‐bearing mice, and histopathological analysis demonstrate that this oxygen‐evolving nanoplatform can elevate singlet oxygen to effectively inhibit tumor growth without obvious damage to major organs. The preliminary results from this study indicate the potential of biocompatible PB@PMO‐Ce6 nanoplatform to elevate O2 and ROS for improving PDT efficacy. Abstract : The integrated, simple, and biocompatible nanoplatform, chlorin e6 conjugated periodic mesoporous organosilica coated prussian blue nanoparticles (PB@PMO‐Ce6), can effectively decompose hydrogen peroxide to evolve oxygen and generate more reactive oxygen species under laser irradiation for enhancing tumor photodynamic therapy.